Monica Perilaku Organisasi Pemerintah Desa Adodo Fordata Dalam Praktik Good Governance - Bormasa, Monica Feronica (SENTRI: Jurnal Riset Ilmiah, 2025)
This article analyzes the organizational behavior of the Adodo Fordata Village government, located in Fordata District, in implementing the principles of good governance. The study employs a descriptive qualitative approach using interviews, observations, and documentation techniques. The findings indicate that the organizational behavior of village officials has been aligned with the principles of transparency, accountability, and participation, although several challenges remain, such as limited capacity of the officials, low participation from youth and women, and limited digital literacy among the community. These findings affirm that village governance is shaped not only by regulations but also by the organizational behavior fostered by the village apparatus.